PENERAPAN METODE DISKUSI KELOMPOK DALAM PEMBELAJARAN KONTEKSTUAL GUNA MENINGKATKAN HASIL BELAJAR IPS EKONOMI SISWA KELAS VII SMPN 2 DOLOPO MADIUN - Novita Erliana Sari (Universitas PGRI Madiun, 2013)
This study aims to determine the presence or absence of the application of learning and improving student learning outcomes VIIB class second semester SMP Negeri 2 Dolopo with the implementation of Contextual Teaching and Learning with Discussion Group Methods on Economic social studies.Subjects were VIIB semester grade SMP Negeri 2 Dolopo which are 32 students consisting of 19 male and 13 female. The procedure consisted of four series of activities done in repeated cycles with two cycles: (1) planning, (2) actions, (3) observation and (4) reflection. Data was collected through observation and tests.The research proves that teachers' ability to apply learning with group discussions to enhance social studies learning outcomes Economic VIIB semester grade SMP Negeri 2 Dolopo Madiun.In the discussion of learning techniques can be known active students during the learning process has increased. This can be shown by (a) Students were attentive and interested in learning to follow an increase in the first cycle 15 students or 46.87% in the second cycle to be 20 students or 62.50%, (b) student activity in an increase in the expression in the first cycle a number of 13 students or 40.62% in the second cycle to 19 children, or 59.37%, (c) student activity in response to what others have increased by 18.75% ie in the first cycle were 13 students or 40, 62% while in the second cycle as many as 19 children, or 59.37%, (d) involvement of the student in asking an increase, in the first cycle as many as 15 children, or 46.87%, on the second cycle increased to 18 children, or 56.25% (e) active students in answering questions has increased in the first cycle were 13 students or 40.62%, to 19 students or 59.37%, (f) student activity in an increase in cooperation, pasa first cycle were 19 students or 59 , 37% in the second cycle to be 24 students or 75%.Judging from the results of learning cycle I and cycle II obtained the following results: (a) the number of students who pass the study in the first cycle were 19 students or 59.37%, while in the second cycle as many as 30 students or 93.75% indicating an increase amounted to 33.82%, (b) from 32 students who take the test activities on the first cycle the total value obtained was 2210, while the second cycle increased to 2655, (c) the value of the average or mean in the first cycle was 70.94, while on the second cycle there is an increase as much as 12.03% to 82.97, (d) the mean or median in the first cycle is 75.357%, while in the second cycle increased to 85.333% showed an increase of 9.976%, (e) mode or value that has the highest frequency in the first cycle was 75, while the mode in the second cycle was 85 showed an increase of 10 points, (f) the lowest value or the minimum in the first cycle was 45, while the lowest score was 55 in the second cycle showed an increase of 10 point, (g) the maximum value in the first cycle was 85, while in the second cycle was 95 showed an increase of 10 points.